Sosialisasi Budidaya Padi Organik Dataran Tinggi di Kabupaten Tasikmalaya - Wahyu Purwakusuma; Desi Nadalia; Yayat Hidayat (Institut Pertanian Bogor, 2024)
The development of organic rice has long been echoed in Indonesia as a sustainable agriculture system to produce healthy food and be environmentally friendly. The lower productivity of organic rice compared to conventional rice, less competitive marketing of organic rice, and limited availability of organic fertilizers in the field are the main reasons for the low adoption and development of organic rice by farmers, such as in the upland organic rice development area in Cipatujah, Tasikmalaya Regency. Socialization of organic rice cultivation techniques through organic fertilizer field schools and organic rice technical culture demonstration plots are efforts to increase farmers' adoption of organic rice. The field school is focused on making good quality organic fertilizer formulations in solid and liquid forms. In contrast, the organic rice cultivation demonstration plot aims to determine the dose of organic fertilizer to support optimal growth and productivity of organic rice plants. The solid organic fertilizer formulation produces good quality organic fertilizer with a pH of 8,54-8,71, C-organic content of 27,87-28,63%, C/N ratio of 18,96 – 21,60, and macronutrient contents (N+P2O5+K2O) of 4,67 – 5,13%. Liquid organic fertilizer (LOF) formulations have not produced excellent quality LOF, primarily related to the low pH (pH <4) and low macronutrient contents (N+P2O5+K2O) of 0,49-2,16%. The growth of organic rice plants with a dose of 3 tons/ha (organic rice I) and 6 tons/ha (organic rice II) is slower than conventional rice (chemical fertilizer). At the same time, plant growth of organic rice III (dose 9 tons/ha) was better than conventional rice in terms of number of tillers and plant height.